2017
DOI: 10.1016/j.drugpo.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Residential eviction and exposure to violence among people who inject drugs in Vancouver, Canada

Abstract: Background People who inject drugs (PWID) experience markedly elevated rates of physical and sexual violence, as well as housing instability. While previous studies have demonstrated an association between homelessness and increased exposure to violence among PWID, the relationship between residential eviction and violence is unknown. We therefore sought to examine the association between residential eviction and experiencing violence among PWID in Vancouver, Canada. Methods Data were derived from two open p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Desmond, An, Winkler, & Ferriss, (Desmond et al., ) also conducted a particularly notable study combining survey and court data for a sizable sample. Other studies reported on prospective cohorts but the temporal relation between variables could not be determined and analyses were based on associations using time‐varying variables (Kennedy et al., ; Zivanovic et al., ). Overall, review of all ten studies revealed the most salient factors related to risk of evictions could be grouped into four categories, by order of the strength of their association reported in the literature: financial hardship (60% of studies), sociodemographic and household characteristics (40% of studies); substance use (40% of studies); and other health problems such as physical and mental conditions (80% of studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Desmond, An, Winkler, & Ferriss, (Desmond et al., ) also conducted a particularly notable study combining survey and court data for a sizable sample. Other studies reported on prospective cohorts but the temporal relation between variables could not be determined and analyses were based on associations using time‐varying variables (Kennedy et al., ; Zivanovic et al., ). Overall, review of all ten studies revealed the most salient factors related to risk of evictions could be grouped into four categories, by order of the strength of their association reported in the literature: financial hardship (60% of studies), sociodemographic and household characteristics (40% of studies); substance use (40% of studies); and other health problems such as physical and mental conditions (80% of studies).…”
Section: Resultsmentioning
confidence: 99%
“…mental and physical health problems) in terms of risk factors for eviction (Van Laere et al., ). Lastly, although violence is not a specific health problem, a Canadian study of people who used illicit drugs found that experiencing violence was independently associated with evictions among both females and males (Kennedy et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This framework hypothesizes that a set of intersecting environments—policy, economic, social, and geographic—constrains the range of choices available to individuals to avoid risky injection-related behaviors. The risk environment framework has been particularly useful for studies investigating the sociostructural antecedents of health and social harm experienced by PWID (Kennedy et al, 2017; Rhodes, 2002; Small, Rhodes, Wood, & Kerr, 2007), and is therefore well-suited to a consideration of the impact of migration on risks associated with drug injecting. Using this framework, we hypothesize that migration contributes to risk environments that may expand the risk for injection initiation among migrants and consequent risks for blood-borne disease transmission and the expansion of syndemics of injecting and blood-borne disease.…”
Section: Introductionmentioning
confidence: 99%